Achievements of PVS (Primo Vascular System) Research from a Historical Perspective - Hoon-Gi Kim (Medical Association of Pharmacopuncture Institute, 2022)
The purpose of this paper is to compare the biological research carried out in North Korea with the modern outcomes in the same field, from a historical perspective. In the 1960s, the group led by Bong-Han Kim asserted the existence of a fundamental circulatory system in the human body. Their findings were introduced in five papers as well as in the newspaper Rodong Sinmun. The size of the group, the range of equipment, and their findings expanded gradually, and the final paper on blood cells would be only published one of over sixty papers reported at that time. In the five papers, some unclear and inconsistent contents were found. Meanwhile, in the 2000s, PVS (primo vascular system) researchers have published over one hundred papers to prove the existence of this novel system. Some trends have emerged in approximately sixty papers as follows: The research on the identification of the anatomical and histological characteristics has gradually expanded to encompass the system's own functioning. Also, new visual results (e.g. before and after dyeing, and its comparison with blood clots) and the exploration of possible medical applications (e.g. cancer metastasis channels or stem cells location) have been proposed. However, it is difficult to identify papers which comprehensively represented the elements claimed by Bong-Han Kim's group. In addition, papers have been published more in alternative or Oriental medicine journals than in Western biomedical journals. It seems necessary to report more existence of the system in one laboratory animal and in more influential journals.